Kurikulum PAI Abad 21: Integrasi Nilai Islam dan Literasi Digital dalam Pembentukan Karakter Siswa - Ahmad Sayyidiman Hamidalloh; Asep Saepul Hamdani (IAIN Batusangkar, 2025)
This study aims to formulate a 21st-century Islamic Religious Education (PAI) curriculum model that integrates Islamic values ​​and digital literacy in building student character. This study employed library research with a qualitative analytical approach. Data were obtained from various national and international literature on PAI curriculum, character education, and digital literacy. Data were then analyzed descriptively to identify patterns of integration of Islamic values ​​with digital competencies. The study's results indicate that a 21st-century PAI curriculum should be directed toward a learning model that combines Islamic teachings, digital literacy skills, and character building through active, collaborative, and technology-based learning strategies. The integration of Islamic values ​​with digital literacy can strengthen the formation of students' religious character, social responsibility, and digital ethics. This research provides a conceptual foundation for developing PAI curriculum policies that are relevant to current needs. Keywords: PAI Curriculum, Digital Literacy, Islamic Values, Student Character, 21st Century